A fully integrated sample preparation strategy for highly sensitive intact glycoproteomics. Issue 5 (10th February 2022) - Yang, Lijun; Liu, Jie; Li, Hua; Liu, Yilian; He, An; Huang, Peiwu; Gao, Weina; Cao, Hua; Xu, Ruilian; Tian, Ruijun
Abstract : A fully integrated spintip-based glycoproteomic technology, termed Intact GlycoSISPROT, was developed for highly sensitive intact glycoproteome analysis with low microgram to nanogram level protein samples. Abstract : A fully integrated sample preparation technology, termed Intact GlycoSISPROT, was developed for the highly sensitive analysis of site-specific glycopeptides. Through integrating all glycoproteomic sample preparation steps into a single spintip, Intact GlycoSISPROT provided a tool for site-specific glycosylation analysis with low micrograms to even nanograms of protein sample.